U UPAYA PEMBINAAN AKHLAQUL KARIMAH BAGI PARA REMAJA ISLAM PADA DAYAH AR-RAUDHAH TAHFIZH AL-QUR’AN KECAMATAN BLANG MANGAT KOTA LHOKSEUMAWE, ACEH-INDONESIA: PEMBINAAN AKHLAQUUL KARIMAH BAGI PARA REMAJA ISLAM PADA DAYAH AR-RAUDHAH TAHFIZH AL-QUR’AN - Diauddin Diauddin; Subki Subki (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service research is to find out the efforts to develop Akhlaqul Karimah for Islamic youth in Dayah Ar-Raudhah Tahfizh Al-qur'an, Blang Mangat District, LhokseumaweAceh-Indonesia, including interviews, discussion, problem solving, exemplary, habituation, advice, and describing the obstacles that affect Ar-Raudhah Tahfizh Al-qur'an, Blang Mangat District, Lhokseumawe City. The subjects in this study were 610 Haizh. While the object of research is 15 Hafizh. The method used is coaching and education. Obstacles that affect the development and education of Islamic youth morality in Dayah Ar-Raudhah Tahfizh Ak-Qur'an are the willingness of some students who are still unfamiliar, the personalities of some students are different and the environment of facilities and infrastructure is still limited.